Effect of temperature on the transverse impact performance of preloaded CFRP wire. (1st January 2020) - Fang, Yawei; Fang, Zhi; Jiang, Ruinian; Jiang, Zhengwen; Zhu, Deju
Abstract: This paper experimentally investigated the effect of temperature on the transverse impact response of preloaded carbon fiber reinforced polymer (CFRP) wire. The CFRP wires with a glass transition temperature of 99 °C were tested in the temperature range of −40 to 80 °C using a drop-weight impact test system. The results show that the maximum impact force, maximum wire tension and transverse deflection at fracture of the wire increased as the temperature increased from −40 to 80 °C, due to the ductility of the resin, effective redistribution of internal stresses and reduced stress concentration in the wire at high temperatures; and the energy dissipating capacity was also improved resulting from the low impact damage at high temperatures. A temperature-dependent function to quantify the effect of temperature on the impact response of CFRP wire was established, and formulas for predicting the impact resistance of preloaded CFRP wires at various temperatures were provided.